Predictions of a continuous hyperplasticity model for Bangkok clay - Likitlersuang, S; Houlsby, G (2007)
The performance of a new constitutive model called 'kinematic hardening modified Cam clay' (KHMCC) is presented. The model is described using the 'continuous hyperplasticity' framework. Essentially this involves an infinite number of yield surfaces, thus allowing a smooth transition between elasticity and plasticity. The framework allows soil models to be developed in a relatively succinct mathematical form, since the entire constitutive behaviour can be determined through the specification of two scalar potentials. An implementation of the continuous hyperplasticity model is also described. The model requires eight parameters plus a viscosity coefficient for rate-dependent analysis. The model is defined in terms of triaxial stress-strain variables for this study, and is used to model monotonic triaxial tests on Bangkok clay. Comparisons of the theoretical predictions with the results of cyclic undrained triaxial compression tests on Bangkok clay are also presented.